Fundamentals of physics - Halliday, David (Wiley, 2005)
Fundamentals of Physics, 7th Edition and the Extended Version, 7th Edition offer a solid understanding of fundamental physics concepts, helping readers apply this conceptual understanding to quantitative problem solving, in a breezy, easy–to–understand style. A unique combination of authoritative content and stimulating applications.